The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su141811311
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Peoples’ Food Systems and Biocultural Heritage: Addressing Indigenous Priorities Using Decolonial and Interdisciplinary Research Approaches

Abstract: The food systems and territories of Indigenous Peoples sustain much of the world’s biodiversity, cultivated and wild, through agroecological practices rooted in Indigenous cosmovision and cultural and spiritual values. These food systems have a critical role to play in sustainability transformations but are widely threatened and have received limited research attention. This paper presents the results of four virtual workshops with Indigenous Peoples: a global workshop and local workshops with communities in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Although Indigenous communities have yet to receive the recognition they deserve, food-security workshops involving Indigenous people and local communities are beginning to shape research agendas 25 -such as those organized under the Colombia Bio programme involving multiple Colombian and British stakeholders, and co-led by colleagues at Kew. By adopting more-holistic and more-sustainable views on the management of nature, and focusing on the relationships between human and non-human species 4 , Indigenous peoples are challenging the status quo of economic growth at the cost of natural capital.…”
Section: Routes To Agrobiodiversitymentioning
confidence: 99%
“…Although Indigenous communities have yet to receive the recognition they deserve, food-security workshops involving Indigenous people and local communities are beginning to shape research agendas 25 -such as those organized under the Colombia Bio programme involving multiple Colombian and British stakeholders, and co-led by colleagues at Kew. By adopting more-holistic and more-sustainable views on the management of nature, and focusing on the relationships between human and non-human species 4 , Indigenous peoples are challenging the status quo of economic growth at the cost of natural capital.…”
Section: Routes To Agrobiodiversitymentioning
confidence: 99%
“…The process of synthesizing traditional knowledge, especially as it pertains to understanding the biosphere, with existing science has been referred to as biocultural innovation in policy circles (Swiderska et al, 2018). We define biocultural innovation as the application of traditional knowledge to improve intergenerational wellbeing while minimizing the depletion of biocultural assets .…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat surprisingly, biocultural innovation has been widely documented in literature outside the field of innovation studies. For example, a review commissioned by the European Union identified 510 biocultural innovations that enhance food security, resilience, livelihoods, and biodiversity (Swiderska et al, 2018). These innovations include the revival of parma , a set of collective farming and knowledge‐sharing practices that address climate challenges and labor shortages in the Himalayas, and the use of Msinduzi tree bark as a low‐cost treatment for wounded livestock in Kenya.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Runa Ayllu includes human beings, domesticated plants, animals, water, etc. ; Sallqa Ayllu comprises wild plants and animals; Auki Ayllu represents the sacred and the ancestors; Ayni signi es reciprocity (11).…”
Section: Introductionmentioning
confidence: 99%